Brand hate: the case of Starbucks in France. Issue 1 (7th January 2019) - Bryson, Douglas; Atwal, Glyn
Abstract : Purpose: The purpose of this paper is to use the concept of brand hate as part of an exploratory study in order to investigate the antecedents and consequences of extreme negative affect within the food category. Design/methodology/approach: The authors employed a mixed research design. A short survey of 324 French business school students identified Starbucks as the most hated food brand (measured in terms of frequency of mentions). In total, 14 semi-structured interviews were conducted with participants who had identified Starbucks as a hated brand. Findings: The research study found that not all consumers feel brand hate at the same level and so-called haters expressed differing severity of hate towards Starbucks, i.e. cold, warm and hot brand hate. Findings revealed that the antecedents of extreme negative affect are to a certain extent dependent on the intensity of brand hate. Consumer reactions were discussed in terms of attachment–aversion relationships which were categorised according to soft and hard brand hate. Research limitations/implications: Future research is required to broaden the conceptual scope of brand hate as a construct and apply it in other domains of research, as well as further clarify antecedents and potential outcomes. The authors accept that the study is limited and specific to Starbucks in France. Further research should therefore broaden the scope of context in which brand hate occurs, for example, expanding the geographical scope of the work to other countries and to other food- and drink-related brands. The authors also accept that the study reflects a relatively homogeneous sample and is thus not representative of the general population. Practical implications: Brand managers need to recognise the risk that brand hate will not only distance former customers, but also spread to existing and future customers. Food brand executives need to therefore consider approaches to address the causes and effects of brand hate. Originality/value: Brand hate within the literature is a very recent phenomenon and studies remain rare. The rise of the so-called activist consumer is an emerging phenomenon within the food sector. The discussion of brand hate within a food context represents a new avenue of research.